2021
DOI: 10.1093/humupd/dmab027
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal outcomes of pregnancies resulting from preimplantation genetic testing: a systematic review and meta-analysis

Abstract: BACKGROUND Preimplantation genetic testing (PGT) includes methods that allow embryos to be tested for severe inherited diseases or chromosomal abnormalities. In addition to IVF/ICSI and repeated freezing and thawing of the embryos, PGT requires a biopsy to obtain embryonic genetic material for analysis. However, the potential effects of PGT on obstetric and neonatal outcomes are currently uncertain. OBJECTIVE AND RATIONALE Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 114 publications
8
26
0
Order By: Relevance
“…Zhang et al [7] found a decreased odds of PPROM in the PGT group, but the difference was not signi cant (7.0 vs. 11.6%, aOR 0.63, 95% CI 0.28-1.42, P = 1.0). Moreover, other previous studies revealed comparable risks regarding PPROM [4,5,7,14,22,23]. However, there is a paucity of available data investigating maternal outcomes of PROM in PGT-induced pregnancies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Zhang et al [7] found a decreased odds of PPROM in the PGT group, but the difference was not signi cant (7.0 vs. 11.6%, aOR 0.63, 95% CI 0.28-1.42, P = 1.0). Moreover, other previous studies revealed comparable risks regarding PPROM [4,5,7,14,22,23]. However, there is a paucity of available data investigating maternal outcomes of PROM in PGT-induced pregnancies.…”
Section: Discussionmentioning
confidence: 83%
“…The unavailability of crucial baseline characteristics may render the conclusion credible. Moreover, two recent systematic reviews and meta-analyses suggested that PGT with TE biopsies was associated with a lower rate of VLBW [4,5]. These two studies are di cult to compare to our study, as they included studies with donor oocyte cycles, cleavage-stage biopsies, and fresh embryo transfers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the one hand, some studies have shown that subfertility itself is the main reason for the adverse perinatal outcomes (3,4). On the other hand, growing evidence suggested that both ART procedures and embryo manipulation in the laboratory may play a vital role (5)(6)(7)(8). Furthermore, recent studies reported that endometrial thickness (EMT) could be involved as well.…”
Section: Introductionmentioning
confidence: 99%
“…With the expanding use of ART, there is a rising concern regarding the safety of these treatments for both mother and child [3]. Hundreds of studies focused on the obstetric and perinatal outcomes of in vitro fertilization (IVF) treatment [4][5][6][7]. However, the incidences differed significantly between studies for the same maternal complication (e.g., gestational diabetes).…”
Section: Introductionmentioning
confidence: 99%